The Institutionalization of Inclusive Migration Pedagogy as an Academic Discipline in the Context of Austrian Teacher Training - Manfred Oberlechner (International Dialogues on Education: Past and Present, 2018)
Since the 2016-17 winter semester, migration has become an essential component of the theoretical and practical teacher training in the central region (Upper Austria, Salzburg) as part of the interdisciplinary unit on diversity and inclusion. Reflective and inclusive migration pedagogy requires therefore extensive self-critical reflection work by teachers and students on recognizing difference and plurality, critically examining structures of discrimination and privilege, such as age, class, education, place of residence, physical and mental disabilities, giftedness, sexual orientation, beliefs, religion, and also racially-motivated dehumanization and ethnic stereotypes. In 2013 the “Federal Framework Law Introducing New Training for Educationalists” was passed in the Austrian National Council, thereby creating the legal basis for the education policy project PädagogInnenbildung NEU (see URL: https://www.bmb.gv.at/schulen/lehr/labneu/index.html; retrieved August 10, 2016).